2022
DOI: 10.1037/ser0000548
|View full text |Cite
|
Sign up to set email alerts
|

Mental health treatment utilization and relationship functioning among male and female OEF/OIF veterans.

Abstract: This study examined whether romantic relationship functioning was associated with mental health treatment utilization in male and female veterans. Veterans (N = 760) enrolled in a longitudinal registry completed self-report measures and a diagnostic interview for posttraumatic stress disorder (PTSD). Mental health treatment utilization data procured from Veterans Affairs administrative records were analyzed over 12 months. For men with PTSD, greater romantic relationship dysfunction was associated with more to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…The findings from the present study are consistent with previous research for male veterans (Harper et al, 2021; Vogt, Danitz, et al, 2019). Although Vogt, Danitz, et al (2019) did not find a predictive effect of intimate relationship functioning for men in mediation models, they found that at the bivariate level, poorer intimate relationship functioning was associated with higher likelihood of mental health service use.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The findings from the present study are consistent with previous research for male veterans (Harper et al, 2021; Vogt, Danitz, et al, 2019). Although Vogt, Danitz, et al (2019) did not find a predictive effect of intimate relationship functioning for men in mediation models, they found that at the bivariate level, poorer intimate relationship functioning was associated with higher likelihood of mental health service use.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast with previous findings for female veterans (Vogt, Danitz, et al, 2019), poorer intimate relationship functioning did not explain increased likelihood of mental health treatment seeking. However, these findings are consistent with Harper et al, 2021. Of note, the present study and the Vogt, Danitz, et al (2019) study used different measures of intimate relationship functioning across studies and participants in the present study had higher PTSD symptom severity than the Vogt, Danitz, et al (2019) sample. These differences may help explain the inconsistent findings across studies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations